Black Titanium Dioxide Nanomaterials in Photocatalysis - Xiaodong Yan; Yong Li; Ting Xia (International Journal of Photoenergy)
Titanium dioxide (TiO2) nanomaterials are widely considered to be state-of-the-art photocatalysts for environmental protection and energy conversion. However, the low photocatalytic efficiency caused by large bandgap and rapid recombination of photo-excited electrons and holes is a challenging issue that needs to be settled for their practical applications. Structure engineering has been demonstrated to be a highly promising approach to engineer the optical and electronic properties of the existing materials or even endow them with unexpected properties. Surface structure engineering has witnessed the breakthrough in increasing the photocatalytic efficiency of TiO2 nanomaterials by creating a defect-rich or amorphous surface layer with black color and extension of optical absorption to the whole visible spectrum, along with markedly enhanced photocatalytic activities. In this review, the recent progress in the development of black TiO2 nanomaterials is reviewed to gain a better understanding of the structure-property relationship with the consideration of preparation methods and to project new insights into the future development of black TiO2 nanomaterials in photocatalytic applications.